Fabrication of multi-junction solar cells (Baghdad Science Journal, 2025)
Fabrication of solar cell prepared by thermal spray and vacuum thermal evaporation method on silicon wafer(n-type) and studying its efficiency. The film have been deposited on three layers(ZnO then CdS and CdTe) on Si and glass respectively.Direct energy gap was calculated and equal to (4.3,3.4,3)eV and indirect energy gap equal to (3.5,2.5,1.5)eV respectively . Efficiency was calculated for the cell of area 2cm2 it was equal to 0.14%.